Interventional device visualization with toroidal transceiver and optically coupled current sensor for radiofrequency safety monitoring. Issue 3 (1st April 2014) - Etezadi‐Amoli, Maryam; Stang, Pascal; Kerr, Adam; Pauly, John; Scott, Greig
<x xml:space="preserve">Abstract</x> Purpose The development of catheters and guidewires that are safe from radiofrequency (RF) ‐induced heating and clearly visible against background tissue is a major challenge in interventional MRI. An interventional imaging approach using a toroidal transmit–receive (transceive) coil is presented. This toroidal transceiver allows controlled, low levels of RF current to flow in the catheter/guidewire for visualization, and can be used with conductive interventional devices that have a localized low‐impedance tip contact. Methods Toroidal transceivers were built, and phantom experiments were performed to quantify transmit power levels required for device visibility and to detect heating hazards. Imaging experiments in a pig cadaver tested the extendibility to higher field strength and nonphantom settings. A photonically powered optically coupled toroidal current sensor for monitoring induced RF currents was built, calibrated, and tested using an independent image‐based current estimation method. Results Results indicate that high signal‐to‐noise ratio visualization is achievable using milliwatts of transmit power—power levels orders of magnitude lower than levels that induce measurable heating in phantom tests. Agreement between image‐based current estimates and RF current sensor measurements validates sensor accuracy. Conclusion The toroidal transceiver, integrated with power and current sensing, could offer a promising platform for safe and effective interventional device visualization. Magn Reson Med 73:1315–1327, 2015. © 2014 Wiley Periodicals, Inc.